Raman microspectroscopy of exhaled breath condensate and urine in workers exposed to fine and nano TiO2 particles: a cross-sectional study - Pelclova, Daniela; Barosova, Hana; Kukutschova, Jana; Zdimal, Vladimir; Navratil, Tomas; Fenclova, Zdenka; Vlckova, Stepanka; Schwarz, Jaroslav; Zikova, Nadezda; Kacer, Petr; Komarc, Martin; Belacek, Jaroslav; et al. (Journal of breath research, 2015)
The health effects of engineered nanoparticles in humans are not well-understood; however experimental data support the theory of oxidative stress promoting fibrogenesis and carcinogenicity. The aim of this study was to detect TiO2 particles in exhaled breath condensate (EBC) and urine samples to ascertain their presence and potential persistence and excretion in urine.EBC and urine samples were collected from 20 workers exposed to TiO2 aerosol; among them, 16 had a higher risk level of exposure (production workers) and four had medium risk level (research workers); in addition to 20 controls. Titanium levels in EBC and urine were analysed using the inductively coupled plasma mass spectrometry (ICP-MS) method. A Raman microspectroscopic analysis was performed in EBC and urine to identify the phase composition of TiO2 particles observed. Aerosol exposure in the workplaces was measured using SMPS and APS spectrometers and P-TRAK and DustTRAK DRX monitors.The median concentration of TiO2 aerosol was 1.98 × 10(4) particles cm(-3), the interquartile range (IQR) was 1.50 × 10(4) - 3.01 × 10(4) particles cm(-3) and the median mass concentration was 0.65 mg m(-3) (IQR 0.46-.0.83 mg m(-3)); 70-82% of the particles were smaller than 100 nm in diameter. In any part of the plant, the median TiO2 air concentration did not exceed the national airborne exposure limit of 10 mg m(-3) for inert dust. Particles of rutile and/or anatase were found in the EBC of exposed workers in 8/20 (40%) of the pre-shift and 14/20 (70%) of the post-shift samples. In the urine of workers, TiO2 particles were detected in 2/20 post-shift urine samples only. The mean concentration of titanium in the EBC in production workers was 24.1 ± 1.8 µg/l. In the research workers the values were below the limit of quantitation; LOQ = 4.0 ± 0.2 µg/l), as well as in the controls. In the urine samples of all of the subjects, titanium was under the limit of detection (LOD = 1.2 µg/l). Raman microanalysis of EBC in the workers confirmed the presence of TiO2 anatase and/or rutile crystal phases in the pre-shift samples and their persistence from previous shifts in the workers.
Keywords: Cross-Sectional Studies; Spectrum Analysis, Raman; vydechnutí; lidé; mužské pohlaví; Oxidative Stress; průřezové studie; Adult; Titanium; Occupational Exposure; Humans; dechové testy; Breath Tests; pracovní expozice; dospělí; oxidační stres; titan; Ramanova spektroskopie; Exhalation; Male